BILATERAL DIFFUSE PSEUDOANGIOMATOUS STROMAL HYPERPLASIA IN A PREGNANT WOMAN: CASE REPORT - Lima, Patricia Taranto Sousa; Cotta, Fernanda Mitre; Silva, Leandro Cruz Ramires da; Lauria, Patricia Bittencourt Marques; Santos, Gabriel Aguiar (Mastology, 2020)
Pseudoangiomatous stromal hyperplasia (PASH) is a benign proliferation of breast stroma, usually described as an incidental microscopic finding. Clinically, it can manifest as a palpable and well-circumscribed mass or, in rare cases, as a diffuse bilateral process, causing massive and rapid breast growth. The most widely accepted theory about PASH is the hormo-nal stimulation of breast myofibroblasts, mainly caused by progesterone. A definitive PASH diagnosis is based on typical findings, such as stromal hyperplasia and slit-like channels. The main clinical differential diagnosis is fibroadenoma or phyllodes tumor and, histologically, low-grade angiosarcoma. This work aims at evaluating the maternal and fetal prognosis of a diffuse PASH case in a pregnant woman. This is the case report of a 27-year-old woman with no comorbidities, previously diagnosed with PASH in January 2018, without clinical repercussion or treatment at the time. In 2019, in the 16th week of her second pregnancy, she noticed a rapid and significant breast growth. In the first trimester, she had a wei-ght gain of 12 kg, and her breasts had a four-fold volume increase, preventing her from performing routine activities, such as standing and walking. Over the days, still with progressive breast tissue growth, she showed a considerable reduction in peripheral breast vascularity, intense pain, hyperemia, skin necrosis, overall worsening, and hemodynamic repercussion. Since this is a case little reported in the literature and given the clinical and hemodynamic conditions of the patient, the treatment chosen was bilateral mastectomy, performed with her consent in October 2019. In the immediate postoperative period, she progressed to fetal death and hemodynamic stabilization in the intensive care unit. After a few days of hospitalization, stable, and with good progress, she was discharged for outpatient follow-up. Anatomopathological results corroborated the PASH diagnosis made in 2018. Data on the final pregnancy outcome and the consequences for mother and fetus will be reported. Data analysis was based on a review of the patient’s medical records. We concluded that each case should be assessed individually, taking into account the clinical, surgical, and obstetric aspects to determine the best workup and therapeutic approach.